Hybrid Work Culture and its Impact on Employee Well-Being: A Conceptual Analysis - Cahyaning Haswari; Gusti Ayu Desy Dwi Cahyani; Ni Luh Putu Widyani Puspitawat; Santi Nururly (PT FORMOSA CENDEKIA GLOBAL, 2025)
Technological developments and changes in post-pandemic work patterns have encouraged organizations to adopt a hybrid work culture that combines remote and in-office work. This article is a conceptual analysis that aims to explain how a hybrid work culture affects employee well-being through the integration of various theoretical foundations, such as Job Demands–Resources Theory, Work–Life Balance Theory, Boundary Theory, and Organizational Support Theory. Findings from various studies indicate that a hybrid work culture provides benefits in the form of flexibility, autonomy, reduced commuting time, and increased work-family integration. However, this work model also presents challenges such as technostress, social isolation, role boundary blurring, and workload intensification. This article synthesizes Q1–Q4 journals to develop a conceptual understanding of the mechanisms by which hybrid work influences psychological, social, and occupational well-being. This analysis identifies three main pathways: (1) the dynamics of job demands and job resources, (2) the interaction of the Work–Life Balance and Boundary Management Pathway, and (3) the Organizational Support Pathway. The article concludes with theoretical implications, practical implications, and a future research agenda.